Examination of synovial fluid and serum following intravenous injections of hyaluronan for the treatment of osteoarthritis in dogs - Canapp, S. O.; Cross, A. R.; Brown, M. P.; Lewis, D. D.; Hernandez, J.; Merritt, K. A.; Tran-Son-Tay, R., D. Sc (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
A randomized, blinded, prospective clinical trial was performed to determine the effects of intravenous (IV) administration of hyaluronan sodium (HA) on serum glycosaminoglycans (GAG) concentrations, synovial fluid (SF) hyaluronan concentrations and viscosity in dogs treated for unilateral rupture of the cranial cruciate ligament. Twenty-two dogs undergoing tibial plateau leveling osteotomy were used in this study. Synovial fluid from both stifles and serum were collected prior to surgery and at 2, 4, and 8 weeks following surgery. Dogs received either 1.0 ml (10 mg) of sodium hyaluronate (treatment group 1; n = 10) or equal volume of 0.9% NaCl (treatment group 2; n = 12), IV immediately, 2 and 4 weeks following surgery. Synovial fluid viscosity was evaluated using a magnetically driven, acoustically tracked, translating-ball rheometer. Synovial fluid HA disaccharide content was measured by fluorophore-assisted carbohydrate electrophoresis. Serum GAG concentrations were measured by alcian blue spectrophotometric assay. Data were analyzed using a Wilcoxon sign rank test (p<0.05). Mean ± SD viscosity (cP) was significantly higher (p=0.011) in SF obtained from the intact stifle (450 ± 604.1) than injured (54.8 ± 60.8) prior to surgery. Mean ± SD HA concentrations (ug/ml) were significantly higher (p=0.02) in synovial fluid obtained from the injured stifles (281.4 ± 145.9) than intact stifles (141.6 ± 132.5). No significant difference was noted within or between treatment groups in SF viscosity, HA concentrations, or serum GAG concentrations at any time following surgery. Stifles with cranial cruciate ligament insufficiency had significant alterations in SF viscosity and HA concentrations.
Keywords: Hyaluronic acid; synovial fluid; osteoarthritis